Middle cerebral artery geometric features are associated with plaque distribution and stroke. (6th November 2018) - Yu, Yan Nan; Li, Ming-Li; Xu, Yu-Yuan; Meng, Yao; Trieu, Harry; Villablanca, J. Pablo; Gao, Shan; Feng, Feng; Liebeskind, David S.; Xu, Wei-Hai
Abstract : Objective: We aimed to investigate the geometric features of the middle cerebral artery (MCA) and their relevance to plaque distribution and ischemic stroke. Methods: We reviewed our institutional vessel wall imaging database. Patients with symptomatic MCA atherosclerosis, asymptomatic MCA atherosclerosis, or without MCA atherosclerosis were included. The MCA geometric features, including M1 segment shape and M1 curve orientation, were defined on magnetic resonance angiography. Plaque distribution and other plaque parameters were identified on vessel wall imaging. The association among MCA geometric features, plaque distribution, and ischemic stroke were analyzed. Results: A total of 977 MCAs were analyzed (87 atherosclerotic symptomatic MCAs, 459 atherosclerotic asymptomatic MCAs, and 431 plaque-free MCAs). Overall, curved M1 segments were the predominant shape across all groups. In 91.1% of curved atherosclerotic MCAs, the plaque involved the inner wall of the curve. Plaque not involving the inner wall was shorter ( p < 0.0001) and thinner ( p = 0.005) compared to plaque involving the inner wall. Inferior plaque was observed in 39.9% of inferior-oriented M1 curves compared to 21.7% in non–inferior-oriented M1 curves ( p < 0.0001). The absence of an inferior-oriented M1 curve (odds ratio 0.45, 95% confidence interval 0.27–0.77) and presence of superior plaque (odds ratio 2.67, 95% confidence interval 1.52–4.67) were independently associated with stroke after adjusting for plaque length and thickness, degree of stenosis, and remodeling ratio. Conclusions: MCA geometric features are associated with plaque distribution and stroke. Our findings provide insight into the vascular pathophysiology of MCA atherosclerosis.